Adult‐type granulosa cell tumor of the ovary: a FOXL2‐centric disease. (11th January 2021) - Pilsworth, Jessica A; Cochrane, Dawn R; Neilson, Samantha J; Moussavi, Bahar H; Lai, Daniel; Munzur, Aslı D; Senz, Janine; Wang, Yi Kan; Zareian, Sina; Bashashati, Ali; Wong, Adele; Keul, Jacqueline; et al.
Abstract: Adult‐type granulosa cell tumors (aGCTs) account for 90% of malignant ovarian sex cord‐stromal tumors and 2–5% of all ovarian cancers. These tumors are usually diagnosed at an early stage and are treated with surgery. However, one‐third of patients relapse between 4 and 8 years after initial diagnosis, and there are currently no effective treatments other than surgery for these relapsed patients. As the majority of aGCTs (>95%) harbor a somatic mutation in FOXL2 (c.C402G; p.C134W), the aim of this study was to identify genetic mutations besides FOXL2 C402G in aGCTs that could explain the clinical diversity of this disease. Whole‐genome sequencing of 10 aGCTs and their matched normal blood was performed to identify somatic mutations. From this analysis, a custom amplicon‐based panel was designed to sequence 39 genes of interest in a validation cohort of 83 aGCTs collected internationally. KMT2D inactivating mutations were present in 10 of 93 aGCTs (10.8%), and the frequency of these mutations was similar between primary and recurrent aGCTs. Inactivating mutations, including a splice site mutation in candidate tumor suppressor WNK2 and nonsense mutations in PIK3R1 and NLRC5, were identified at a low frequency in our cohort. Missense mutations were identified in cell cycle‐related genes TP53, CDKN2D, and CDK1 . From these data, we conclude that aGCTs are comparatively a homogeneous group of tumors that arise from a limited set of genetic events and are characterized by the FOXL2 C402G mutation. Secondary mutations occur in a subset of patients but do not explain the diverse clinical behavior of this disease. As the FOXL2 C402G mutation remains the main driver of this disease, progress in the development of therapeutics for aGCT would likely come from understanding the functional consequences of the FOXL2 C402G mutation.